Microtensile bond strength of resin cements to 3-D printed and milled temporary restorative resins = Resistencia de unión en microtracción de cementos resinosos a resinas para provisionales impresas y fresadas - Soto Montero, Jorge 1985-
To evaluate the microtensile bond strength (μTBS) of two resin cements to 3D printed and milled CAD/CAM resins used for provisional fixed partial dentures. Blocks (5 x 5 x 5 mm) of three 3D-printed resins (Cosmos3DTemp / Yller; Resilab3D Temp / Wilcos and SmartPrint BioTemp, / MMTech) were printed (Photon, Anycubic Technology Co.). A milled material (VitaCAD-Temp, VITA) was used as control. Half the specimens were sandblasted and the rest were untreated. Two blocks were bonded with the corresponding resin cement: PanaviaV5 (Kuraray Noritake) and RelyX Ultimate (3M Oral Care). After 24 hours, the bonded blocks were sectioned into 1 x 1 mm side sticks. Half the beams were tested for μTBS and the other half was thermocycled (5000 cycles, 30s dwell-time, 5s transfer time) before μTBS testing. A four way Generalized Linear Model (material*sandblasting*cement*aging) analysis was applied. VITA exhibited the lowest μTBS, regardless of the cement, sandblasting and thermocycling. Sandblasting significantly improved the μTBS of VIT, especially after aging, but did not improve the μTBS of 3D printed resins. Sandblasting was not beneficial for 3D printed resins, although is crucial for adhesive cementation of milled temporary resins. Airborne particle abrasion affects the integrity of 3D-printed resins, without producing a benefit on the microtensile bond strength of these materials. However, sandblasting is crucial to achieve a high bond strength on milled temporary resins.